Analisis Karakteristik dan Uji Bioaktivitas Bakteri Rizosfer PGPR (Plant Growth Promoting Rhizobacteria) Isolat Kalasey - Stephen Christiano Lengkong; Parluhutan Siahaan; Agustina Monalisa Tangapo (Universitas Sam Ratulangi, 2022)
PGPR fertilizer in Kalasey North Sulawesi has been used for horticultural crop cultivation. Data on the types of bacteria and the ability of bacterial activity to stimulate plant growth in local areas have never been published. This study aims to analyze the characteristics and to test the bioactivity of the bacterial isolates Kalasey. The method is carried out by isolating, identifying, and testing IAA production, phosphate dissolution, and nitrogen fixation of bacteria isolates. The results showed that there were 9 bacterial isolates by characteristic macroscopic colony. IAA production ranged between 13.22-39.52 mg/L. The solubilization index in dissolving phosphate ranges from 1.0-2.9. Nitrogen fixation showed 4 isolates were positive on Ashby media. Microscopic observation showed 8 isolates were gram negative and 1 isolate was gram positive. The shapes of bacteria vary from round, rod, circular chain, and straight chain rod. In conclusion, local soil bacteria isolated are soil bacteria with varied characteristics and have potential activity capabilities in the development of local PGPR fertilizers.Keywords: Soil Bacteria; Bioactivity; Rhizosphere; Growth PromotingABSTRAKPupuk organik cair PGPR Desa Kalasey, Minahasa, Sulawesi Utara telah dimanfaatkan untuk budidaya tanaman hortikultura. Data tentang jenis-jenis bakteri dan kemampuan aktivitas bakteri dalam memacu pertumbuhan tanaman di daerah lokal belum pernah terpublikasi. Penelitian ini bertujuan untuk menganalisis karakteristik dan menguji bioaktivitas dari isolat-isolat bakteri terkait. Metode dilakukan dengan mengisolasi, mengidentifikasi, dan melakukan pengujian produksi IAA, pengujian pelarutan fosfat, dan pengujian fiksasi nitrogen. Hasil penelitian menunjukkan terdapatnya 9 isolat bakteri. Produksi IAA berkisar antara 13,22-39,52 mg/L. Indeks solubilisasi dalam pelarutan fosfat berkisar 1,0-2,9. Fiksasi nitrogen menunjukkan 4 isolat positif pada media Ashby. Pengamatan mikroskopis menunjukkan 8 isolat termasuk bakteri Gram negatif dan 1 isolat termasuk bakteri Gram positif. Bentuk-bentuk bakteri bervariasi dari bulat, batang, bulat berantai, dan batang lurus berantai. Kesimpulannya, bakteri tanah daerah lokal yang diisolasi merupakan bakteri-bakteri tanah dengan karakteristik yang beragam dan memiliki kemampuan aktivitas yang berpotensi baik dalam pengembangan pupuk PGPR lokal.